Teaching Writing Using Jumbled Texts Game - Sri Widiastuti; Sudarsono Sudarsono; Zainal Arifin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe present research was designed to examine the effectiveness of a jumbled-texts game to teach writing descriptive texts. It was a pre-experimental study. The subjects were Year-7 students of SMPN 21 Pontianak in Academic Year 2017/2018. Jumbled texts game is an activity to improve students’s writing descriptive text. This game helped the students of SMPN 21 Pontianak in organizing the generic structure of a descriptive text. The sample of this research was 40 students in class VII A. The data revealed that jumbled texts game is an effective technique that can be used by the teacher as an intereting way to teach writing descriptive text in the class. The findings showed that a jumbled-texts game improved the students’ skill in writing a descriptive text. The student’s mean score of pre test was 52.37 and the student’s mean score of post test was 63.37. furthermore, the effect size of the treatment was 0.83. It is categorized as highly effective since it is higher than 0.8. the teacher might need some appropriate variations in apllying this game depending on the situation and condition found in the classroom.Keywords: Descriptive Text, Jumbled Texts Game, Pre Experimental Research, Teaching Writing